Efeitos psíquicos da intervenção assistida por equino em criança: estudo de caso - Ferreira, Paula Damiana Marcondes (2023)
Introduction: Animal-assisted interventions (AAI) that use the equine species as a mediator represent an emerging field of research. These animals can act as social facilitators and potential catalysts for contact between humans. Objective: To investigate the psychic effects of equine-assisted intervention in children. Method: Research of qualitative, descriptive and exploratory nature, developed in the modality of case study, being obeyed the ethical norms for studies with living beings. Sample: child with 10 years and 3 months, female and motivated for equine-assisted intervention. Procedure: Pre-IAA phase: Semidirected interview with the teacher, interview with the mother and application of the DrawingStory procedure (D-E) with the subject. Phase IAA: individual activities in equine management: 1) approximation and brushing, 2) feeding, cleaning of stalls, bath 3) basic encilhamento, 4) conduction of the animal and 5) guided mount. The stages of the intervention phase were filmed. Post-IAA phase: reapplication of the D-E procedure. Conclusion: There is evidence, in the case studied, that human-equine interaction aroused singular psychic effects; especially in the results of the post-IAA D-E procedure. Therefore, it is suggested that studies on AAI (predominantly developed with dogs) were conducted with horses